Clinical characteristics and the influence of rs1800470 in patients with Camurati-Engelmann disease - Liang, Hanting; Jiajue, Ruizhi; Qi, Wenting; Liu, Wei; Chi, Yue; Jiang, Yan; Wang, Ou; Li, Mei; Xing, Xiaoping; Xia, Weibo (Frontiers in Endocrinology, 2022)
Background: Camurati-Engelmann disease (CED) is a sclerosing bone dysplasia caused by transforming growth factor β1 (TGFB1) gene variants. Objective: We aim to summarize the clinical characteristics and the efficacy of glucocorticoids in 14 individuals with CED, and explore the correlation between the phenotype and the SNP of rs1800470 (c.29C>T). Methods: Clinical, biochemical, radiological, and therapeutic data were collected from 14 patients. DNA was extracted for TGFB1 variants detection by Sanger sequencing. Results: The median onset and record age were 3.0 and 16.1 years, respectively. All patients manifested bone pain and decreased subcutaneous fat tissue. Inflammatory markers increased in over 60% of patients, and the median erythrocyte sedimentation rate (ESR) was 1.40 (0.50~3.67) of the upper limit of normal (ULN), and the median high sensitivity C reactive protein (hsCRP) was 1.71 (0.48~12.56) of ULN. There was a positive correlation between ESR and hsCRP (rs=0.806, p=0.003). Both ESR and hsCRP were negatively correlated with the levels of hemoglobin (HGB), calcium, and creatinine, but positively correlated with the level of alkaline phosphatase. Four known variants of TGFB1 were identified, including p.Tyr171Cys, p.Arg218Cys, p.Arg218His, and p.Cys225Arg. Moreover, 35.7% and 28.6% of them carried the heterozygous and homozygous SNP of c.29C>T, called C/T and T/T groups, respectively, but 35.7% of them were without c.29C>T (C/C group). The onset age, anthropometric data, percentages of different clinical manifestations, and biochemical parameters were comparable among the three groups. But there were increasing trends in levels of HGB and calcium and decreasing trends in ESR and hsCRP among C/C, C/T, and T/T groups in turn. Glucocorticoid improves the two inflammatory markers among CED patients. Conclusion: The phenotype of CED is highly heterogeneous. There is no clear genotype-phenotype correlation, but it seems to have better trends of biochemical parameters in patients with CED carrying the T allele of rs1800470.